2007
DOI: 10.1094/ats-2007-1119-01-rs
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Synthetic Hydraulic Fluid on Warm-Season Turfgrass

Abstract: Synthetic hydraulic fluid, which was developed for turf equipment in 2005, was compared to traditional hydraulic oils for its potential to cause turf injury. Effects of fluid type, volume, and temperature on area of injury, percent necrosis, and time to healing were investigated at Edison College in 2005‐2006 via three experiments on hybrid bermudagrass (Cynodon dactylon L. [Pers.] × C. transvaalensis Burtt‐Davey) or seashore paspalum (Paspalum vaginatum O. Swartz). Synthetic fluid applied on container‐grown ‘… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 3 publications
1
7
0
Order By: Relevance
“…Thus, we conclude that B100 and B20 spills generally result in less turf damage and faster recovery compared with PD spills. This is consistent with research on the effects of vegetable‐based hydraulic fluid spills (Berndt, 2007).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Thus, we conclude that B100 and B20 spills generally result in less turf damage and faster recovery compared with PD spills. This is consistent with research on the effects of vegetable‐based hydraulic fluid spills (Berndt, 2007).…”
Section: Discussionsupporting
confidence: 91%
“…A related study (Berndt, 2007) evaluated the effect of petroleum, synthetic (polyalkylene‐glycol), and vegetable‐oil hydraulic fluids applied at various temperatures and volumes on the necrosis and recovery of warm‐season turfgrasses. As expected, the synthetic hydraulic fluid resulted in the least necrosis and the most rapid recovery; however, vegetable‐oil‐based hydraulic fluid resulted in less necrosis and faster recovery than petroleum‐based hydraulic fluid.…”
Section: Background and Rationale For The Studymentioning
confidence: 99%
“…Fluids that are less dense than water may also be buoyed by soil moisture, limiting infiltration and increasing spreading behavior (Simmons and Keller, 2005). Differences in density may partially explain differences in IA between nonpolar oils, with PHO always producing larger IA than VHO for a given spill volume (Berndt, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Testimonials suggested that flushing SHO with water immediately after a spill eliminated turf injury (D. da Costa, personal communication, 2007). Spill volume is an important factor as injury area increases with spill volume (Berndt, 2007). Season may be a significant influence on the dynamics of IA (Berndt, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation